Observational Validation of Parameterized Gravity Waves From Tropical Convection in the Whole Atmosphere Community Climate Model. Issue 7 (8th April 2021) - Alexander, M. J.; Liu, C. C.; Bacmeister, J.; Bramberger, M.; Hertzog, A.; Richter, J. H.
Abstract: Tropical gravity waves that are generated by convection are generally too small in scale and too high in frequency to be resolved in global climate models, yet their drag forces drive the important global‐scale quasi‐biennial oscillation (QBO) in the lower stratosphere, and models rely on parameterizations of gravity wave drag to simulate the QBO. We compare detailed properties of tropical parameterized gravity waves in the Whole Atmosphere Community Climate Model version 6 (WACCM6) with gravity waves observed by long‐duration superpressure balloons and also compare properties of parameterized convective latent heating with satellite data. Similarities and differences suggest that the WACCM6 parameterizations are excellent tools for representing tropical gravity waves, but the results also suggest detailed changes to the gravity wave parameterization tuning parameter assumptions that would bring the parameterized waves into much better agreement with observations. While WACCM6 currently includes only nonstationary gravity waves from convection, adding gravity waves generated by the steady component of the heating that are stationary relative to moving convective rain cells is likely to improve the simulation of the QBO in the model. The suggested changes have the potential to alleviate common biases in simulated QBO circulations in models. Plain Language Summary: This work examines the connections between tropical rain cells and small‐scale atmospheric waves (called gravity waves) in the National Center for Atmospheric Research's Whole Atmosphere Community Climate Model version 6 (WACCM6). Comparisons with high‐resolution observations of tropical rain and tropical gravity waves lead us to suggest new methods for future simulations with WACCM6 that are likely to improve WACCM6 representation of interannual wind changes and their impacts on tropical precipitation and winter season weather in the Northern Hemisphere. Key Points: WACCM subgrid‐scale gravity wave and deep convection properties are validated using tropical observations Optimal subgrid‐scale convective fraction and heating depth parameters are found through the validation Adding the missing stationary component of gravity waves above convection would likely improve QBO simulations